Sistem Informasi Tenaga Pengajar (Dosen Kontrak) pada Fakultas Ilmu Sosial dan Ilmu Politik Universitas Syiah Kuala - Yanawati; Idwan, Harry; Fathurrahmad (Computer Journal, 2023)
Higher education institutions need an efficient information system in managing teaching staff data, including contract lecturers, to ensure institutional effectiveness and productivity. However, there are still many universities that do not have adequate information systems, resulting in obstacles in administrative and management activities. Therefore, this research aims to design an Information System for Teaching Personnel (Contract Lecturers) at the Faculty of Social and Political Sciences, Syiah Kuala University. In this research, an analysis of the current system was carried out, the design of a new web-based system, and the implementation of a prototype-based development method were carried out. The research results show that the new information system can improve efficiency, security and accuracy in managing teaching staff data. Suggestions for further system development were also presented to improve the quality and flexibility of the system